Rationale and trial design of NATALEE: a Phase III trial of adjuvant ribociclib + endocrine therapy versus endocrine therapy alone in patients with HR+/HER2− early breast cancer - Slamon, Dennis J.; Fasching, Peter; Hurvitz, Sara; Chia, Stephen; Crown, John; Martín, Miguel; Barrios, Carlos H.; Bardia, Aditya; Im, Seock Ah; Yardley, Denise A.; Untch, Michael; Huang, Chiun Sheng; et al. (Therapeutic Advances in Medical Oncology, 2023)
Background: Ribociclib has demonstrated a statistically significant overall survival benefit in pre- and postmenopausal patients with hormone receptor positive/human epidermal growth factor receptor 2 negative (HR+/HER2−) advanced breast cancer. New Adjuvant Trial with Ribociclib [LEE011] (NATALEE) is a trial evaluating the efficacy and safety of adjuvant ribociclib plus endocrine therapy (ET) versus ET alone in patients with HR+/HER2− early nonmetastatic breast cancer (EBC). Methods/design: NATALEE is a multicenter, randomized, open-label, Phase III trial in patients with HR+/HER2− EBC. Eligible patients include women, regardless of menopausal status, and men aged ⩾18 years. Select patients with stage IIA, stage IIB, or stage III disease (per the anatomic classification in the AJCC Cancer Staging Manual, 8th edition) with an initial diagnosis ⩽18 months prior to randomization are eligible. Patients receiving standard (neo)adjuvant ET are eligible if treatment was initiated ⩽12 months before randomization. Patients undergo 1:1 randomization to ribociclib 400 mg/day (3 weeks on/1 week off) +ET (letrozole 2.5 mg/day or anastrozole 1 mg/day [investigator’s discretion] plus goserelin [men or premenopausal women]) or ET alone. Ribociclib treatment duration is 36 months; ET treatment duration is ⩾60 months. The primary end point is invasive disease-free survival. Discussion: The 36-month treatment duration of ribociclib in NATALEE is extended compared with that in other adjuvant cyclin-dependent kinases 4 and 6 (CDK4/6) inhibitor trials and is intended to maximize efficacy due to longer duration of CDK4/6 inhibition. Compared with the 600-mg/day dose used in advanced breast cancer, the reduced ribociclib dose used in NATALEE may improve tolerability while maintaining efficacy. NATALEE includes the broadest population of patients with HR+/HER2− EBC of any Phase III trial currently evaluating adjuvant CDK4/6 inhibitor treatment. Trial registration: ClinicalTrials.gov identifier: NCT03701334 (https://clinicaltrials.gov/ct2/show/NCT03701334)
CRIS-Team Scopus Importer:2023-06-30
Keywords: adjuvant therapy; CDK4/6 inhibitors; HR+/HER2– early breast cancer; NATALEE; ribociclib